Dynamic Knowledge Transfer and Knowledge Development for Product and Process Design Teams - Özkan-Seely, Gülru F.; Gaimon, Cheryl; Kavadias, Stylianos (Manufacturing and Service Operations Management, 2015)
We consider a manager who invests in knowledge development of a product and a process design team as well as knowledge transfer between teams throughout a new product development (NPD) project. Knowledge development at a particular time (e.g., prototyping and experimentation) increases a team’s level of knowledge at that time. In contrast, the recipient’s benefits from knowledge transfer may be lagged because of the difficulties in articulating and documenting knowledge as well as the challenges regarding its interpretation and application. Over time, as each team embeds knowledge in the NPD project, the levels of product and process performance increase, thereby increasing the net revenue earned at the product launch time. In a key contribution to the literature, analytic conditions are given that characterize the dynamic rates at which knowledge development and knowledge transfer occur throughout the project. We show that the investment in knowledge development for each team and knowledge transfer between teams may be constant, front-loaded, back-loaded, U-shaped, or the peak rate may be delayed over time. As such, we show how concurrent engineering is optimally pursued throughout the NPD project.